The Influence of organizational culture on employee retention in foreign owned banks in Kenya - Nduru, P. J. (Strathmore University, 2024)
Kenya's banking sector faces significant employee turnover due to issues such as cultural unawareness, heavy workloads, poor environments, insecurity, work-life imbalance, and unsatisfactory salaries. These challenges are intertwined with organizational infrastructure and organizational culture. Skilled professionals often switch jobs for better pay and improved conditions, compounding the problem. This study sought to examine the influence of organizational culture on employee retention in the Foreign owned banks in Kenya. It delved into the impact of organizational cultural dimensions (Hofstede's Power Distance, Masculinity, Individualism, and Uncertainty Avoidance) on retention. The research drew from Hofstede’s cultural dimensions theory, supplemented by the social exchange theory. Using a descriptive research design, the study targeted the thirteen registered foreign owned banks in Kenya. This study adopted a quantitative research design; specifically, descriptive cross-sectional survey technique. The researcher administered structured questionnaires electronically using google forms from a selected sample of 187 respondents. Data collected was analyzed using descriptive statistics, correlation analysis and regression analysis. The results showed that among the four dimensions of culture, power distance and masculinity had a positive influence on employee retention while uncertainty avoidance and individualism had a negative influence. This study contributes to theory by building on the existing literature on Hofstede’s cultural dimensions theory by boosting the understanding of the various dimensions of culture and the possible effect that each cultural dimension could have on employee retention. In addition, this study will also inform organizational policy development surrounding issues such as compliance, customer engagement, and employee development. The findings of this study were limited to the classifications of the dimensions of culture and employee retention adopted by the researcher. The study was also limited to data collected using cross- sectional surveys, and only the foreign owned banks and were studied. Future studies could address these limitations. Keywords: Employee retention; Organizational culture; Hofstede’s cultural dimensions; Kenya; Banking sector;
Full - text thesis